Interns or workers? China's student labor regime - Chan, J; Pun, N; Selden, M (Asian Studies Association of Hong Kong, 2015)
In the summer of 2010, Taiwanese-based Foxconn Technology Group- the world's largest electronics manufacturer- utilized the labor of 150,000 student interns from vocational schools at its facilities all over China. Foxconn is one of many global firms utilizing student intern labor. Far from being freely chosen, student internships are organized by the local state working with enterprises and schools, frequently in violation of the rights of student interns and in violation of Chinese law. Foxconn, through direct deals with government departments, has outsourced recruitment to vocational schools to obtain a new source of student workers at below minimum wages. The goals and timing of internships are set not by student educational or training priorities but by the demand for products dictated by companies. Based on fieldwork in Sichuan and Guangdong between 2011 and 2012 and follow-up interviews in 2014, as well as analysis of the Henan government's policies on internships, we find that the student labor regime has become integral to the capital-state relationship as a means to assure a lower cost and flexible labor supply for Foxconn and others. This is one dimension of the emerging face of Chinese state capitalism.